Multimorbidity: A global public health challenge - Rajović Nina; Milić Nataša (Medicinski Podmladak)
According to available data, at least 50 million people in the European Union live with multimorbidity. The trend of an aging population, accompanied by the adoption of unhealthy lifestyles and the rising incidence of chronic illnesses, results in a increase in the prevalence of multimorbidity. This has proved to be a major challenge for healthcare systems worldwide. Future healthcare should be proactive and include a preventive component for patients at risk of multimorbidity. A multitude of challenges linked to multimorbidity, such as the provision of informal treatment, limited knowledge among the general population and healthcare professionals, particularly in middleand low-income nations, underscore the need for comprehensive reform and restructuring of the healthcare system. In order to advance towards the establishment of high-quality health systems, it is imperative to prioritize the key concerns of health care users, which primarily include the provision of continuous and adequate treatment, enhanced treatment outcomes, and fostering trust in the health system. To effectively address the strain on healthcare systems caused by multimorbidity, it is imperative to prioritize the establishment of well-structured, adequately equipped, and appropriately trained primary care teams. Furthermore, primary healthcare should establish a network with other levels in the healthcare system, including the system of education and social protection programs. This integration should extend to the entire local community, aiming to enhance the well-being of both the individual and the community as a whole. Multimorbidity has shown to be a significant challenge for healthcare systems worldwide, making a need for guidance among health policy makers, health managers and physicians in defining and implementing interventions aimed at decreasing the burden associated with multimorbidity.